The strategies used in the teaching-learning process before and after the advent of the COVID-19 pandemic: concepts of accounting students and teachers (Research, Society and Development, 2022)
Higher education in Brazil undergoes constant changes and the use of teaching-learning methods and strategies is of paramount importance, especially with the beginning of the COVID-19 pandemic across the planet. In this sense, the present study was developed with the objective of identifying, in the perception of students and teachers of the Undergraduate Course in Accounting Sciences, which are the main teaching strategies applied in accounting education and the most effective before and with the advent of the pandemic of Corona Virus. This study is characterized as a quantitative research in relation to the research problem, with a descriptive approach in relation to the objective. As for the data collection procedures, a survey was carried out. The results showed that the teaching strategy that students and teachers considered most effective and most used in classes before and with the advent of the pandemic was solving exercises and that the most used and effective didactic resource, according to students and teachers, before and with the pandemic it's exercises. It was verified in the students' view, before the pandemic and with the advent, the best way for teachers to develop skills, in students, and encouraging study/research and exercises.